Proceedings of the 10th Annual Conference on Genetic and Evolutionary Computation 2008
DOI: 10.1145/1389095.1389362
|View full text |Cite
|
Sign up to set email alerts
|

An efficient SVM-GA feature selection model for large healthcare databases

Abstract: This paper presents an efficient hybrid feature selection model based on Support Vector Machine (SVM) and Genetic Algorithm (GA) for large healthcare databases. Even though SVM and GA are robust computational paradigms, the combined iterative nature of a SVM-GA hybrid system makes runtime costs infeasible when using large databases. This paper utilizes hierarchical clustering to reduce dataset size and SVM training time, multi-resolution parameter search for efficient SVM model selection, and chromosome cachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, for mutation types (Gaussian, switching, and sparsity) we followed the methods of phase I in addition to optimization with simple validation. Given the guidance of [43, 44], we considered various values for C and gamma; the default for gamma=1.0 was best. We also confirmed that the default value for epsilon=0.1 was reasonable for our data.…”
Section: Methodsmentioning
confidence: 99%
“…However, for mutation types (Gaussian, switching, and sparsity) we followed the methods of phase I in addition to optimization with simple validation. Given the guidance of [43, 44], we considered various values for C and gamma; the default for gamma=1.0 was best. We also confirmed that the default value for epsilon=0.1 was reasonable for our data.…”
Section: Methodsmentioning
confidence: 99%
“…• National and regional level: At this level, how to represent and keep the data of patients typically is a critical research issue [31] . Finding useful information from the data of a national or regional medical center [26,44,55,56] has been a promising research trend in recent years because a data analytics system can verify the assumption and find out interesting patterns from a sufficient amount of data. Moreover, metaheuristic-based data mining algorithms can be used to find out the relationships between symptoms and particular disease, or even the relationships between cause and effect of human behaviors and disease.…”
Section: Research Issues Of Healthcarementioning
confidence: 99%
“…Optimization of SVM parameters were performed by evaluating a set of cost-gamma combinations defined using uniform design (UD) method [48]. UD is a technique that scatters a set of points uniformly across the cost-gamma landscape, proposed to alleviate the computational loads associated with the search for the optimal cost-gamma pair [49]. This search process begins by initializing a 30-points UD (global) search across the defined costgamma landscape.…”
Section: Ga-svmmentioning
confidence: 99%